Revolusi Budaya Ngopi: Cafe Modern Sebagai Sarana Pengembalian Cara Ngopi Zaman Dulu - Nazala Zaikumar Elfa Rizqi; Destri Aulia Wulandari; Dinda Putri Maharani (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research discusses how to restore the coffee culture of ancient people and its relationship with modern cafes that exist today. In ancient times, people drank coffee by producing the ingredients themselves, from growing the coffee to the brewing process. However, as time progressed, instant coffee emerged which made people start consuming instant coffee because the manufacturing process was practical, the price was relatively cheap and the taste had many innovations. This research uses a systems theory perspective by Walter Buckley and is reinforced by Niklas Luhmann's General Systems Theory. According to him, this systems theory focuses on the relationship of various processes in a social system. The research method used is a qualitative research method with an ethnographic approach. The research results show that many cafes that have been established today have brought back the coffee culture of ancient people. This can be proven by making coffee starting from the coffee beans to the blooming process or brewing the coffee using a coffee maker.